Recovering local equilibrium from three‐dimensional compatible finite element solutions - Moitinho de Almeida, J. P.; Maunder, E. A. W. (International journal for numerical methods in engineering, 2020)
SUMMARY We study the application to compressible and incompressible three‐dimensional elasticity problems of the technique that we proposed in 2009 for the recovery of equilibrated stresses from compatible finite element solutions. The case of finite elements with linear displacement approximations, for which the partitioned systems of loads are not initially balanced in terms of rotational equilibrium, addressed in 2012, is also considered. The article includes a presentation of the implementation details, a study of the convergence in terms of the energy of the error, and a characterization of the solutions obtained.